Scleroderma, Myositis and Related Syndromes 2018
DOI: 10.1136/annrheumdis-2018-eular.6030
|View full text |Cite
|
Sign up to set email alerts
|

AB0814 Sodium thiosulfate 10% intralesional to treat calcinosis in patients with systemic sclerosis and dermatomyositis: case series

Abstract: BackgroundCalcinosis is a frequent complication of systemic sclerosis and dermatomyositis, causing local pain, joint mobility reduction, ulcerations, secondary infections and disability. Currently, there is no effective treatment to calcinosis, but the use of topical dressing or intralesional sodium thiosulfate (STS) has showed promising results.ObjectivesTo evaluate efficacy of intralesional STS 10% in calcinosis of patients with dermatomyositis and systemic sclerosis.MethodsProspective and open-labbed study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Healing lesions may be prone to infection (9%, emerging mainly from the skin microbiome) due to softened calcifications [10] and injury caused by the injection. Some patients experienced less pain after completed therapy (median VAS scale reduction of 1, range 0-5), despite unsuccessful size reduction of calcifications [21]. Twelve patients reported by Winter et al [22] (with control lesions) and Tonial et al [21] demonstrated no significant change in size after 3-8 IL-STS injections, although low doses and long injection intervals could disadvantage the treatment efficacy in these studies.…”
Section: Stsmentioning
confidence: 81%
See 2 more Smart Citations
“…Healing lesions may be prone to infection (9%, emerging mainly from the skin microbiome) due to softened calcifications [10] and injury caused by the injection. Some patients experienced less pain after completed therapy (median VAS scale reduction of 1, range 0-5), despite unsuccessful size reduction of calcifications [21]. Twelve patients reported by Winter et al [22] (with control lesions) and Tonial et al [21] demonstrated no significant change in size after 3-8 IL-STS injections, although low doses and long injection intervals could disadvantage the treatment efficacy in these studies.…”
Section: Stsmentioning
confidence: 81%
“…A total of 410 articles were retrieved from the search. Additionally, ten more studies were added after the manual screening of the reference sections [10,[17][18][19][20][21][22][23][24][25]. Eight articles were excluded at the eligibility stage due to reporting patients described in other included studies [20,26,27] or insufficient data [24,25,[28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation